2016
DOI: 10.1186/s13229-016-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Basic and complex emotion recognition in children with autism: cross-cultural findings

Abstract: BackgroundChildren with autism spectrum conditions (ASC) have emotion recognition deficits when tested in different expression modalities (face, voice, body). However, these findings usually focus on basic emotions, using one or two expression modalities. In addition, cultural similarities and differences in emotion recognition patterns in children with ASC have not been explored before. The current study examined the similarities and differences in the recognition of basic and complex emotions by children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 104 publications
(138 reference statements)
8
79
2
3
Order By: Relevance
“…In particular, this numerosity was determined taking into account the sample size of previous studies in the field, the complexity of the task that was presented, and its feasibility for individuals with LFA. Despite being influenced by group composition, recruitment areas, and available means, the sample size selected was consistent with previous literature on the subject (Moore et al, 1997;Atkinson et al, 2004;Hubert et al, 2007;Parron et al, 2008;Atkinson, 2009;Annaz et al, 2010Annaz et al, , 2012Fridenson-hayo et al, 2016). Eventually, we successfully included in the study 69 subjects (27 TD; 25 HFA; 17 LFA) that completed the task.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, this numerosity was determined taking into account the sample size of previous studies in the field, the complexity of the task that was presented, and its feasibility for individuals with LFA. Despite being influenced by group composition, recruitment areas, and available means, the sample size selected was consistent with previous literature on the subject (Moore et al, 1997;Atkinson et al, 2004;Hubert et al, 2007;Parron et al, 2008;Atkinson, 2009;Annaz et al, 2010Annaz et al, , 2012Fridenson-hayo et al, 2016). Eventually, we successfully included in the study 69 subjects (27 TD; 25 HFA; 17 LFA) that completed the task.…”
Section: Resultsmentioning
confidence: 93%
“…In ASD, the investigation of differences in recognizing emotional PLDs and FLDs was limited to adults and showed an impaired recognition of both PLDs and FLDs (Atkinson, 2009). Poorer accuracy in recognizing emotional FLDs of BM have been shown in children with ASD (Fridenson-hayo et al, 2016). Yet, differences in recognizing emotional FLDs and PLDs have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…34,39 Furthermore, some studies have found ASD deficits in recognizing certain emotions more often than others, such as happiness and neutrality, 40 surprise, 36,38 and fear, 36,39,40 as well as deficits in judgment of more complex social stimuli, such as trustworthiness, shame, and approachability. 34,36,38,41 We outline our hypotheses and objectives below.…”
mentioning
confidence: 99%
“…Specifically, face processing has been identified as a possible marker of impairment in social cognition within ASD. This impairment has been associated with difficulties in recognizing the emotions of others [Lozier, Vanmeter, & Marsh, ; Uljarevic & Hamilton, ] and has been observed cross‐culturally [Friedenson‐Hayo et al, ].…”
Section: Introductionmentioning
confidence: 99%